ANALISIS IMPLEMENTASI KEBIJAKAN KOTA LAYAK ANAK BIDANG KESEHATAN RAMAH ANAK - Gerry Katon Mahendra (Universitas 'Aisyiyah Yogyakarta, 2017)
The rise of violence and a lack of fulfillment of the basic needs of children indicate the role of government in ensuring basic rights has not been optimal. Policy needed to accommodate the rights of the child. child-friendly city policy is expected to answer the question of fulfillment of children. The research objective knowing implementation of health children sector in the city of Yogyakarta 2016. Type of research using quantitative descriptive by spreading the questionnaire. Results of research policy implementation child-friendly city policy, child-friendly health care is GOOD (score 2.77). The findings in this study of a total of 18, just 4 health centers that implement child-friendly health services. The lack of cooperation between stakeholders in the implementation of child-friendly health care policy.Maraknya kasus kekerasan dan kurangya pemenuhan kebutuhan dasar anak mengindikasikan peran pemerintah dalam menjamin hak dasar belum optimal. Diperlukan kebijakan untuk mengakomodir hak anak. Kebijakan Kota Layak Anak (KLA) diharapkan mampu menjawab persoalan pemenuhan hak anak. Tujuan penelitian, menganalisis implementasi kebijakan KLA di Kota Yogyakarta tahun 2016. Jenis penelitian menggunakan deskriptif kuantitatif dengan menyebar angket. Hasil penelitian pelaksanaan kebijakan KLA bidang kesehatan ramah anak di Puskesmas yang menerapkan pelayan kesehatan ramah anak BAIK (skor 2.77). Temuan dalam penelitian, dari 18 Puskesmas baru empat yang melaksanakan pelayanan kesehatan ramah anak. Minimnya kerjasama antar stakeholders pada implementasi kebijakan kesehatan ramah anak.